Organosolv lignin aggregation behaviour of soluble lignin extract from Miscanthus x giganteus at different ethanol concentrations and its influence on the lignin esterification - Hamzah, Muhammad Hazwan; Bowra, Steve; Cox, Philip (SpringerOpen, 2021)
Background: Lignin is the second most abundant naturally occurring biopolymer from lignocellulosic biomass. While there are several lignin applications, attempts to add value to lignin are hampered by its inherent complex and heterogenous chemical structure. This work assesses the organosolv lignin aggregates behaviour of soluble lignin extract derived from Miscanthus × giganteus using diferent ethanol concentrations (50%, 40%, 30%, 20%, 10% and 1%). The efect of two diferent lignin concentrations using similar ethanol concentration on the efcacy of esterifcation was studied. Results: Overall, particle size of lignin analysis showed that the particle size of lignin aggregates decreased with lower ethanol concentrations. 50% ethanol concentration of soluble lignin extract showed the highest particle size of lignin (3001.8 nm), while 331.7 nm of lignin particle size was recorded at 1% ethanol concentration. Such fndings of particle size correlated well with the morphology of the lignin macromolecules. The lignin aggregates appeared to be disaggregated from population of large aggregates to sub-population of small aggregates when the ethanol concentration was reduced. Light microscopy images analysis by ImageJ shows that the average diameter and circularity of the corresponding lignin macromolecules difers according to diferent ethanol concentrations. The dispersion of lignin aggregates at low ethanol concentration resulted in high availability of hydroxyl group in the soluble lignin extract. The efcacy of the lignin modifcation via esterifcation was evidenced directly via FTIR using the similar ethanol concentration of soluble lignin extract at diferent lignin concentrations. Conclusion: This study provided the understanding of detail analysis on particle size determination, microscopic properties and structural insights of lignin aggregates at wider ethanol concentrations. The esterifed lignin derived at 5 mg/mL is suggested to expand greater lignin functionality in the preparation of lignin bio-based materials.